2022
DOI: 10.1128/aac.01535-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Proteasome-Targeting Arylsulfonamide with Potential for the Treatment of Chagas’ Disease

Abstract: Phenotypic screening identified an arylsulfonamide compound with activity against Trypanosoma cruzi , the causative agent of Chagas’ disease. Comprehensive mode of action studies revealed that this compound primarily targets the T. cruzi proteasome, binding at the interface between β4 and β5 subunits that catalyse chymotrypsin-like activity. A mutation in the β5 subunit of the proteasome was associated with resistance to compound 1 , while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…A similar approach was used to confirm the role of CPSF3, a protein involved in messenger RNA processing, as the target of AN15368, a new benzoxaborole analog with anti-parasitic activity and apparent low toxicity, and to identify its nature as a prodrug metabolized by a parasite serine carbopeptidase. 82 The same method was used to identify the β4/β5 interface in the parasite’s proteasome as the target of a new arylsulfonamide previously shown to present in vitro anti-parasitic activity, 37 , 104 confirming results from previous studies that suggested that inhibition of proteasome activity is an exploitable pathway in the treatment of kinetoplastid infections. 105 , 106 At least five compounds targeting CPSF3 or the kinetoplastid proteasome are currently in development pipelines for the identification of new treatments against kinetoplastid parasites, and three of these are potentially useful in the treatment of Chagas disease (see corresponding section below).…”
Section: Drug Screening Strategies Used To Identify Potentially Usefu...supporting
confidence: 69%
“…A similar approach was used to confirm the role of CPSF3, a protein involved in messenger RNA processing, as the target of AN15368, a new benzoxaborole analog with anti-parasitic activity and apparent low toxicity, and to identify its nature as a prodrug metabolized by a parasite serine carbopeptidase. 82 The same method was used to identify the β4/β5 interface in the parasite’s proteasome as the target of a new arylsulfonamide previously shown to present in vitro anti-parasitic activity, 37 , 104 confirming results from previous studies that suggested that inhibition of proteasome activity is an exploitable pathway in the treatment of kinetoplastid infections. 105 , 106 At least five compounds targeting CPSF3 or the kinetoplastid proteasome are currently in development pipelines for the identification of new treatments against kinetoplastid parasites, and three of these are potentially useful in the treatment of Chagas disease (see corresponding section below).…”
Section: Drug Screening Strategies Used To Identify Potentially Usefu...supporting
confidence: 69%
“…Quantitative measures of drug resistance can also be important in determining whether specific mutations are likely to have a detrimental impact in a clinical setting. Cas9-based editing has been applied to T. brucei CPSF3, providing insights into selective anti-trypanosomal action 52 , and to the Trypanosoma cruzi proteasome, revealing cross-resistance between arylsufonamides and distinct anti-leishmanials 130 . Oligonucleotide targeting, which is Cas9 independent, has also now been used to edit priority drug targets in trypanosomatids 131 .…”
Section: Compounds and Targetsmentioning
confidence: 99%
“…The title compound (330 mg, 70.8%) was synthesized from 29b according to method F as a white solid. 1 (39). The title compound (1.20 g, 80%) was synthesized from 4,6-dichloro-1H-pyrazolo [3,4-d]pyrimidine (38) according to method F as a crude product.…”
Section: -Chloro-5-methyl-4-(3-(pyridin-2-yl)pyrrolidin-1-yl)-5h-pyrr...mentioning
confidence: 99%
“…Despite many interesting and fruitful approaches to identify new chemical entities for the treatment of T. cruzi infection in the past decade, further research is still required to address CD, with the clear goal of obtaining an effective, orally bioavailable, affordable, and safe molecule effective in both the acute and chronic phases of the disease.…”
Section: Introductionmentioning
confidence: 99%